Der Tagesgang des Niederschlages auf den Hawaii-Inseln - Schroeder, Thomas A.; Kilonsky, Bernard J.; Kreisel, Werner (ERDKUNDE, 1978)
A detailed study has been made of hourly rainfall records in the Hawaiian Islands. Rainfall frequency distributions reflect the complexity of interaction between the trade winds and large islands. The mountainous Hawaiian Islands exert a profound influence over the local weather. Diurnal rainfall variation is specifically influenced by me soscale circulations. The masses of Mauna Loa and Mauna Kea produce mountain-sea breeze oscillations which overwhelm the prevailing trade winds. On the Hilo (windward) slopes the result is a strengthened nocturnal maximum near Hilo which disappears upslope. On leeward slopes sea breezes produce afternoon rainfall maxima. To a lesser degree Haleakala produces similar effects on Maui. The windward slopes of the smaller islands have diurnal cycles which are reminiscent of open ocean conditions. Leeward sections of smaller islands have less clear cut diurnal cycles although several locations are influenced by local sea breezes. Oahu is unique in that it has two formidable mountain masses which lie normal to the trade wind direction. The Koolau range effectively desiccates air crossing it; convective activity produces afternoon effects over the Waianaes and the central saddle near Wahiawa is in between the two. First harmonic curves were fit to the hourly distributions with useful results for nearly all stations. The major contributor to lack of fit is less than 12-hour interval from minimum to maximum. An indicator of amplitude of diurnal cycle is the ratio of maximum to minimum frequency. As might be expected the largest ratios occurred in the locations of strongest mesoscale circulations, especially the Kona sea breeze. Extremely wet stations such as near mountains which do not penetrate the trade inversion (Oahu, Kauai, West Maui) have small ratios. With the exception of a few extremely dry locations the partition of data into light rain days (hourly totals 2.5 mm) produced no additional insight. This matches an observed feature of island median rainfall distributions. While storms provide much quantitative rainfall in leeward areas, they do not alter the island distribution, which is dominated by daily events.